(In)complete neutralization in Western Andalusian Spanish - María del Saz (Estudios de Fonética Experimental)
The present study addresses the occurrence of affrication in clusters other than /st/ in Western Anda- lusian Spanish, by means of production and perception tasks comprising /st/, /kt/, and /pt/. Our find- ings reveal incomplete neutralization in production, given that /kt/ presented a higher closure ratio and a lower VOT ratio than /pt/ and /st/. In perception, the three clusters were similarly labeled according to a pattern: /st/ > /kt/ > /pt/. Certain parameters such as closure and VOT ratios and center of gravity seemed to have an influence on perception. These results indicate that neutralization may be complete in perception and incomplete in production.